2018
DOI: 10.22159/ijpps.2018v10i2.23779
|View full text |Cite
|
Sign up to set email alerts
|

28-HOMOCASTASTERONE: A NOVEL DIETARY PHYTO KETO OXYSTEROL MODULATING TESTICULAR STEROID METABOLISM AND LxR mRNA EXPRESSION IN DIABETIC RAT

Abstract: Objective: Present study aims to investigate 28-homocastasterone (28-HC) influences on testicular tissue in the normal and diabetic rat.Methods: Induction of diabetes was achieved by single peritoneal injection of streptozotocin (60 mg/kg b. wt) followed by 28-HC (100 µg/150 gm body weight) administration by oral gavage for 15 consecutive days to experimental rats. 3β-hydroxysteroid dehydrogenase, 17β-hydroxysteroid dehydrogenase activities, testosterone level, Liver X Receptor (LxR) mRNA expression, malondial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was found that brassinosteroid keto isoform homocastasterone exhibited antiglycemic activity in diabetic rats and also improved RBC, WBC, platelets, hemoglobin levels, and reduced cell damage and inflammatory disorders such as inflammatory bowel disease, allergic reactions, and leukemia or myeloproliferative neoplasms in humans [131].…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
“…It was found that brassinosteroid keto isoform homocastasterone exhibited antiglycemic activity in diabetic rats and also improved RBC, WBC, platelets, hemoglobin levels, and reduced cell damage and inflammatory disorders such as inflammatory bowel disease, allergic reactions, and leukemia or myeloproliferative neoplasms in humans [131].…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%